HUBUNGAN LINGKUNGAN FISIK RUMAH DAN PERILAKU MEMBUKA JENDELA DENGAN KEJADIAN PENYAKIT TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS SAKRA TAHUN 2021 - Hamidah, Baiq; Desimal, Iwan; Ariany, Farida (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Tuberculosis is a communicable disease which is caused by mycobacterium tuberculosis bacteria. This study aimed to know the relationship between home physical environment and windows opening behavior toward tuberculosis disease. Type of the study was analytic observational with case control approach. Univariate analysis used frequency distribution formula and bivariate analysis used Coefficient Contingency C formula with significance level α<0.05. Determination sample by using total sampling (saturated sample), with a total sample of 122 samples, namely 61 case samples and 61 control samples. The variables studied are humidity, lighting, ventilation area, and window opening behavior. The result of univariate analysis on case sample, frequency distribution did not meet humidity requirements, was 33 (54.1%), lighting 29 (47.5%), ventilation area 39 (63.9%), windows opening behavior 44 (72.1%). In sample control frequency distribution did not meet humidity requirements, was 13 (21.3%), lighting 22 (36.1%), ventilation area 29 (47.5%), windows opening behavior 20 (32.8%). The result of bivariate analysis on humidity variable value of C=0.252, p=0.004<0.05; lighting value of C= 0.116, p= 199>0.05, ventilation area value of C=0.163, p=0.068>0.05, windows opening behavior value of C=0.367, p=0.000<0.05. The conclusion of the study is that variables associated with tuberculosis are humidity, the value of C=0.252, p=0.004<0.05 and windows opening variable, the value of C 0.36, p=0.000<0.05. The variables of lighting, ventilation area did not have any relationship to tuberculosis at Sakra Public Health Center. It is suggested to the Head of UPT BLUD of Sakra Public Health Center to make policies to prevent transmission of tuberculosis through effort to improve home physical environment and counseling on windows opening behavior.